2017
DOI: 10.3892/mmr.2017.6282
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1 upregulation promotes myocardiocyte proliferation and suppresses apoptosis during heart development

Abstract: Previous studies have investigated the role of microRNAs (miRs) in heart development to reveal the miRNA mechanism of action in congenital heart disease (CHD) in children. The present study aimed to investigate the role of miR‑1 in heart development in P19 cells. The mRNA level for miR‑1 in P19 cells was detected before or after cardiomyocyte differentiation, using reverse transcription‑quantitative polymerase chain reaction analysis. Expression of cardiomyocyte differentiation markers was also analyzed. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Dysfunction of the respiratory chain further increases ROS production, which creates a positive feedback loop and exacerbates the damage. Moreover, insufficient energy production and myocardial apoptosis are conducive to ventricular remodeling, ultimately leading to the occurrence of HF (Liu et al, 2017). The results of this study suggest that the increased ROS production in myocardial tissues of ISO-induced cardiomyopathy rats is accompanied by the destruction of the mitochondrial ultrastructure, decreased mitochondria numbers, reduced activities of mitochondrial respiratory chain I, II, III, IV, and decreased ATP production; however, PER intervention can ameliorate the disruption of mitochondria, attenuate decreases in mitochondrial numbers, improve respiratory chain function, and increase myocardial ATP content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of the respiratory chain further increases ROS production, which creates a positive feedback loop and exacerbates the damage. Moreover, insufficient energy production and myocardial apoptosis are conducive to ventricular remodeling, ultimately leading to the occurrence of HF (Liu et al, 2017). The results of this study suggest that the increased ROS production in myocardial tissues of ISO-induced cardiomyopathy rats is accompanied by the destruction of the mitochondrial ultrastructure, decreased mitochondria numbers, reduced activities of mitochondrial respiratory chain I, II, III, IV, and decreased ATP production; however, PER intervention can ameliorate the disruption of mitochondria, attenuate decreases in mitochondrial numbers, improve respiratory chain function, and increase myocardial ATP content.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Zhang et al, 2015;Liu et al, 2017) suggest that OS-induced production of excessive ROS induces apoptosis, and myocardial apoptosis causes ventricular remodeling, which ultimately leads to HF (Zhang et al, 2015;Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…miR-1 has been suggested to have an important impact on cardiac pathology. 15 Liu et al 6 suggested that miR-1 overexpression contributed to proliferation but inhibited apoptosis of cardiomyocytes in heart development. However, accruing studies have revealed that miR-1 promoted cardiomyocytes apoptosis and suppressed proliferation under glucose or oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…5 Moreover, previous study suggests that miR-1 contributes to increase of proliferation and inhibition of apoptosis of cardiomyocytes during heart development. 6 However, the function of miR-1 in regulating hypoxia injury as well as its mechanism remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Under the condition of OS, the increase of ROS production in mitochondria may lead to abnormal mitochondrial respiratory chain function, leading to reduced ATP synthesis and activation of endogenous apoptotic pathways. In addition, insu cient energy production and cardiomyocyte apoptosis contribute to ventricular remodeling and ultimately lead to HF (25). The results of this study indicate that the production of ROS in the myocardial tissue of ISO-induced cardiomyopathy rats is accompanied by a decrease in mitochondrial respiratory chain I, II, III, IV activity and ATP production.…”
Section: Discussionmentioning
confidence: 64%